Gemcitabine Plus Anlotinib Is Effective and Safe Compared to Gemcitabine Plus Docetaxel in Advanced Soft Tissue Sarcoma - Liu, Zhiyong; Wang, Xin; Wang, Jiaqiang; Zhang, Peng; Li, Chao; Wang, Bangmin; Liu, Guancong; Yao, Weitao (Frontiers in Oncology, 2022)
Objective The aim of this study is to compare gemcitabine (G) plus docetaxel (D) versus G plus anlotinib (A) for advanced soft tissue sarcoma (STS). Methods We retrospectively investigated 122 patients with locally advanced or metastatic STS who were treated with either G+D or G+A between July 2016 and October 2021 and compared the efficacy and toxicity of G+D and G+A. The primary endpoints were median progression-free survival (PFS) and the proportion of patients with grade ≥3 adverse events. We also analyzed differences in the clinical efficacy of G+D and G+A in leiomyosarcoma, and the differences in the clinical efficacy of G+D and G+A as first-line therapy. Results Overall, 122 patients were included (81 patients receiving G+D and 41 patients receiving G+A) with a median age of 55 years. The main histological types are leiomyosarcoma, undifferentiated pleomorphic sarcoma, and liposarcoma. After a median follow-up of 25 months, PFS did not differ between patients treated with G+D and those treated with G+A (median PFS: 5.8 months and 6.8 months, p = 0.39), and overall survival (OS) was similar (median OS: 14.7 vs. 13.3 months, p = 0.75) with a similar objective response rate (18.5% vs. 14.6%, p = 0.17), whereas the proportion of patients with grade ≥3 adverse events treated with G+D was significantly higher than those treated with G+A (68% vs. 44%, p < 0.05). Subgroup analysis of leiomyosarcoma patients (47.5% of the patients) and first-line treatment patients (46.7% of the patients) shows that PFS was not significantly different between the two groups (LMS: median PFS: 6.5 months vs. 7.5 months, p = 0.08; first-line treatment: median PFS: 6.2 months vs. 7.1 months, p = 0.51). Conclusion Compared with gemcitabine plus docetaxel for advanced STS, gemcitabine plus anlotinib achieved a similar response rate on median PFS and OS, but lower toxicity. These results suggest that gemcitabine plus anlotinib may be an effective and safe strategy for advanced STS.